Supervision of Land Deed Officials (PPAT) on Deeds of Sale and Purchase Before Payment of BPHTB - Jani, Rafsan (Jurnal Konstatering, 2024)
The signing of a deed of sale and purchase by a Land Deed Making Officer (PPAT) before payment of Land and Building Acquisition Fee (BPHTB) has caused a polemic of law and professional ethics. This practice not only violates applicable legal provisions, but also has the potential to harm the state in terms of tax revenue. The purpose of this study is to analyze the Implementation of Supervision and Guidance of Land Deed Officials Who Sign Deeds of Sale and Purchase Before Payment of BPHTB in North Kolaka Regency and to analyze the legal responsibility of Land Deed Officials who sign Deeds of Sale and Purchase before payment of BPHT in North Kolaka Regency. The problem-solving approach method used by the author is an empirical approach method, namely a method of data collection carried out by examining secondary data against primary data in the field and examining existing facts in line with observations in the field which are then reviewed based on related laws and regulations because the existing laws are in fact made, and determined by humans who live in society to research related to the Implementation of Supervision and Guidance for PPAT Who Signed the Sale and Purchase Deed Before Payment of BPHTB in North Kolaka Regency. The results of the study can be concluded that the implementation of guidance and supervision of the Advisory and Supervisory Board of PPAT is to visit several PPATs and obtain several findings related to several PPATs in North Kolaka and provide guidance related to PPAT job regulations, socialization of regulations concerning the PPAT code of ethics and supervision, namely in the form of supervision of the implementation of PPAT positions and enforcement of legal regulations in accordance with regulations in the field of PPAT